Influencia de los contenidos digitales en la escritura de los estudiantes de comunicación social de la Universidad Técnica de Babahoyo Extensión Quevedo, año 2022 - Mosquera Zambrano, Jordan Alberto (2022)
Digital contents generate a change in the communication models, thanks to the technological advances of the last 10 years that have innovated in the educational, social and cultural fields. Digital contents are born as a meeting of people, known or unknown, who interact with each other, redefining the group and feeding it back. This idea is linked to the Web 2.0 culture, which is nothing more than a new idiom for what we used to define as doing something in a group. The great advantage of group work is that it thrives on the efforts of all those involved. Day after day it is more difficult for teenagers to live without the constant use of social networks, because of the time they spend in these new ways of communication, the different spelling rules are lost, thus causing a serious problem in teenagers, negatively affecting the language and their spelling. Every day it is more difficult for teenagers to live without the constant use of digital content, because of the time they spend in these new ways of communication they are losing the different spelling rules, thus causing a serious problem in adolescents negatively affecting the language and its spelling.